Osteoclast-like stromal giant cells in breast cancer likely belong to the spectrum of immunosuppressive tumor-associated macrophages - Sajjadi, Elham; Gaudioso, Gabriella; Terrasi, Andrea; Boggio, Francesca; Venetis, Konstantinos; Ivanova, Mariia; Bertolasi, Letizia; Lopez, Gianluca; Runza, Letterio; Premoli, Alice; Lorenzini, Daniele; Guerini-Rocco, Elena; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Breast cancer with osteoclast-like stromal giant cells (OSGC) is an exceedingly rare morphological pattern of invasive breast carcinoma. The tumor immune microenvironment (TIME) of these tumors is populated by OSGC, which resemble osteoclasts and show a histiocytic-like immunophenotype. Their role in breast cancer is unknown. The osteoclast maturation in the bone is regulated by the expression of cytokines that are also present in the TIME of tumors and in breast cancer tumor-associated macrophages (TAMs). TAMs-mediated anti-tumor immune pathways are regulated by miRNAs akin to osteoclast homeostasis. Here, we sought to characterize the different cellular compartments of breast cancers with OSGC and investigate the similarities of OSGC with tumor and TIME in terms of morphology, protein, and miRNA expression, specifically emphasizing on monocytic signatures. Methods and results: Six breast cancers with OSGC were included. Tumor-infiltrating lymphocytes (TILs) and TAMs were separately quantified. The different cellular populations (i.e. normal epithelium, cancer cells, and OSGC) were isolated from tissue sections by laser-assisted microdissection. After RNA purification, 752 miRNAs were analyzed using a TaqMan Advanced miRNA Low-Density Array for all samples. Differentially expressed miRNAs were identified by computing the fold change (log2Ratio) using the Kolmogorov-Smirnov test and p values were corrected for multiple comparisons using the false discovery rate (FDR) approach. As a similarity analysis among samples, we used the Pearson test. The association between pairs of variables was investigated using Fisher exact test. Classical and non-classical monocyte miRNA signatures were finally applied. All OSGC displayed CD68 expression, TILs (range, 45-85%) and high TAMs (range, 35-75%). Regarding the global miRNAs profile, OSGC was more similar to cancer cells than to non-neoplastic ones. Shared deregulation of miR-143-3p, miR-195-5p, miR-181a-5p, and miR-181b-5p was observed between OSGC and cancer cells. The monocyte-associated miR-29a-3p and miR-21-3p were dysregulated in OSGCs compared with non-neoplastic or breast cancer tissues. Conclusions: Breast cancers with OSGC have an activated TIME. Shared epigenetic events occur during the ontogenesis of breast cancer cells and OSGC. Still, the immunophenotype and miRNA profiles of the different cellular compartments suggest that OSGC likely belong to the spectrum of M2 TAMs.